Association between oophorectomy and depression in patients with comorbidities: A nationwide cohort study in Taiwan - Kent Yu-Hsien Lin; Ching-Ying Chou; Cherry Yin-Yi Chang; Wu-Chou Lin; Lei Wan (Elsevier, 2020)
Objective: This study investigated the long-term rates of depression after oophorectomy for benign gynecological conditions with or without comorbidities. Materials and methods: This retrospective cohort study examined data from the National Health Insurance Research Database (NHIRD) involving 8199 women aged ≥20 years who underwent unilateral or bilateral oophorectomy for benign gynecological conditions (cases) between 2000 and 2013 (index date). A second cohort consisted of 32,796 women who did not undergo oophorectomy (controls) who were matched 4:1 to cases by age and index year. The follow-up time was more than 10 years. For all participants, the analysis accounted for comorbidities including hypertension, diabetes mellitus, hyperlipidemia, stroke, chronic obstructive pulmonary disease (COPD), chronic liver disease and cirrhosis, chronic kidney disease, and anxiety. Crude hazard ratios, adjusted hazard ratios, and 95% confidence intervals (CIs) were calculated according to multivariable Cox proportional hazard regression models adjusting for age, comorbidity, and the combination of oophorectomy with one comorbidity. Results: Our results show that unilateral or bilateral oophorectomy, whether performed by laparotomy or laparoscopy, increases the overall risk of depression (aHR: 1.36, 95%CI: 1.19-1.55). Compared with controls, women aged <50 years had a significantly higher incidence of depression. Having diabetes (aHR: 1.66, 95%CI: 1.09-2.51), hypertension (aHR:1.56, 95%CI:1.14-2.14), hyperlipidemia (aHR: 1.46, 95%CI: 1.04-2.05), stroke (aHR: 1.91, 95%CI: 1.01-3.60), COPD (aHR: 2.06, 95%CI: 1.3-3.26), chronic liver cirrhosis (aHR: 1.99, 95%CI:1.52-2.61), or anxiety (aHR: 5.01, 95%CI: 3.74-6.70) increased higher risk of depression compared with not having these comorbidities after oophorectomy. The likelihood of depression was highest within the first 6 years following oophorectomy (3-5years:aHR:1.26, 95%CI:1.00-1.58). Conclusions: Oopherectomy increases the overall risk of depression. We offer useful information for surgical decision-making and preoperative assessments of women undergoing oophorectomy. It is concluded that a synergistic effect exists between oophorectomy and the comorbidities. Post-surgery, physicians should carefully evaluate the risk of depression developing amongst women with comorbidities. A postoperative follow-up time of at least 6 years is recommended, as this period was associated with a significantly higher rate of depression during our over 10-year follow-up.